Transformation of Consumer Buying Interest After The Pandemic Covid-19 Pandemic in Shopee E-Commerce - Azzahra, Naoera Aliya; Elsa Mahardika; Erna Apriani; Indra Permana; Abdul Latif (Sumber Belajar Sejahtera, 2025)
Digital marketing has become an essential strategy for influencing consumer purchasing decisions in the digital era. Technological and internet advancements have transformed how companies interact with consumers, enabling wider reach through platforms like social media, websites, and e-commerce. Besides enhancing brand awareness, digital marketing influences consumer preferences and behavior by offering personalized and tailored experiences. This study examines the impact of price, social media usage, and location on consumer buying interest on the Shopee platform. Using a quantitative method, data were collected through electronic questionnaires from 100 respondents and analyzed using SmartPLS with multiple linear regression. The results reveal that price significantly and positively influences buying interest (coefficient: 0.503, t-statistic: 6.234, P-value: 0.000). Social media usage, however, shows a positive but insignificant effect (coefficient: 0.138, t-statistic: 1.404, P-value: 0.164). Location also demonstrates a significant positive effect on purchase intention (coefficient: 0.316, t-statistic: 3.634, P-value: 0.000). The study concludes that price and location are critical factors in shaping consumer purchasing decisions on e-commerce platforms, particularly in the post-pandemic context. These findings underscore the importance of competitive pricing and convenient delivery as key drivers of purchase intention, providing valuable insights for businesses to refine their marketing strategies and adapt to evolving consumer preferences.